Exploiting proximity in event-based Middleware for collaborative mobile applications - MEIER, RENE; CAHILL, VINNY (Springer Berlin / Heidelberg, 2003)
Middleware supporting event-based communication is widely recognized as being well suited to mobile applications since it naturally accommodates a dynamically changing population of interacting entities and the dynamic reconfiguration of the connections between them. STEAM is an event-based middleware designed for use in ad hoc networks. STEAM differs from other event-based middleware in that its architecture does not rely on the presence of any separate infrastructure, event notification filters are distributed, and filtering may be applied to functional and non-functional attributes. In particular, filters may be applied to either the subject or the content of an event notification, or to non-functional attributes, such as location and time. Filters may be used to define geographical areas within which event notifications are valid, thereby bounding the propagation of these notifications. Such proximity-based filtering represents a natural way to filter events of interest in mobile applications. This paper describes the architecture and implementation of STEAM and its use of proximity-based filtering. In particular, we show how proximity-based filtering can be used to reduce the number of events delivered to collaborative mobile applications.
Lecture Notes in Computer Science
Distributed Applications and Interoperable Systems
PUBLISHED
Keywords: mobile applications; mobile applications